Landscape architecture a very short introduction - Thompson, Ian H. 1955- (Very short introductions, 2014)
Landscape architecture plays an important role in shaping the places in which we live and work. But what is it? Landscape architects are involved, amongst other things, in the layout of business parks, the reclamation of derelict industrial sites, the restoration of historic city parks, and the siting and design of major pieces of infrastructure such as motorways, dams, power stations, and flood defences, as well as the planning of parks and gardens. Taking a historical perspective, Ian Thompson looks at both the roots of landscape architecture and the people that established it